The role of monoclonal antibodies in the therapeutic strategy of chronic lymphocytic leukemia (Hematology Meeting Reports, 2009)
Monoclonal antibodies (MoAb) have led to a profound shift in the therapeutic scenario of CLL. Alemtuzumab and rituximab are the most active MoAbs to date, and their single-agent activity has been established both in previously untreated and in relapsed patients with CLL. MoAbs act through unique mechanisms distinct from conventional cytotoxic chemotherapy: engagement of restricted cell-surface antigens, activation of intracellular pro-apoptotic signaling pathways, and activation of effector functions, including components of the complement system and antibody-dependent cellular cytotoxicity through the activation of natural killer cells and macrophages through their IgG fragment C receptors.